VIDEOGAMES E FICÇÃO CIENTÍFICA: REPRESENTAÇÕES DO FUTURO CAÓTICO NAS SÉRIES HALF-LIFE E METAL GEAR SOLID - Paula, Cássio Remus de (2017)
The current thesis seeks to demonstrate the relations of dystopias and scientific fiction notions with the virtual game series Half-Life and Metal Gear Solid, in addiction to understanding significant game titles in their influence. Such notions are problematized from the historical research of the scientific fictions, derived from literature and cinema, such as the own science conceptions during the 19th and 20th centuries. Therefore, theoretical-methodological sources referred to the ludism, cinema and representation are used in order to establish the notions of dystopia presented in the specified games, in a link with the concepts of the pessimistic future existed in the scientific and artistic imaginary.